Effects of acupuncture on mental health of migraine patients: a systematic review and meta-analysis - Zhao Li; Jie Feng; Shao Yin; Xin Chen; Qicheng Yang; Xu Gao; Deya Che; Li Zhou; Hui Yan; Yue Zhong; Fengya Zhu (BMC, 2023)
Abstract Background Migraine is a neurological disease characterized by moderate to severe headache and various neurological symptoms. It is often cause mood and anxiety disorders that can seriously affect quality of life. Acupuncture has been claimed to have a role in treating neuropsychiatric disorders and is becoming increasingly popular. However, it remains unclear whether current evidence is sufficient to support acupuncture in improving mental health in migraine patients. Objectives This systematic review and meta-analysis aimed to investigate the effect of acupuncture on the management of pain and mood disorders in patients with migraine. Methods We searched PubMed, Cochrane Library, Embase, Web of Science, Chinese National Knowledge Infrastructure (CNKI) and Wan Fang Data Knowledge Service Platform for reports, conferences and academic papers published before January 1, 2022. Randomized controlled trials (RCTs) including acupuncture, sham acupuncture and medication for migraine were included. Stata 16.0 software and Cochrane RoB2.0 were used for data processing and migration risk analysis. Result Thirteen randomized controlled trials containing 1766 migraine patients were included in the present study, the results showed that compared with sham acupuncture and medication, acupuncture seemed to have advantage in improving SAS (WMD: -5.64;95% CI: -10.89, -0.39; p = 0.035) and SDS (WMD: -4.65; 95% CI: -9.25, -0.05; p = 0.048) in migraine patients. And it seems to be more effective in improving MH (SMD: 0.77; 95% CI: 0.19, 1.35; p = 0.009), VAS (SMD: -1.06; 95% CI: -1.73, -0.4; p = 0.002;) and MSQ (WMD: 4.76; 95% CI: 2.36, 7.15; p < 0.001) than sham acupuncture and medication. Conclusion The present results suggest that, compared with Western medicine and sham acupuncture, acupuncture seems to be able to effectively improve anxiety and depression in migraine patients.And it may be more effective in improving SF36-mental health, VAS and MSQ than shame acupuncture or Western medicine. The results of this study need to be verified by higher quality RCTs.